Application of a model to predict algal behaviour in rivers at Ömerli reservoir, Turkey - Kahraman Özen, Sevil. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2014., 2014)
The occurrence of small populations of algal blooms in lakes, reservoirs, rivers and other freshwater environments is natural. However, under favourable conditions, the population size can increase dramatically and the algae may accumulate at the freshwater surface as a concentrated bloom. As a result of the bloom occurrence, water resources and water-body users can face the problems of reduced aesthetic quality, emission of unpleasant odours, blocking of water-filtration systems and release of toxins into the water. The apparent increase in the frequency of bloom events is a symptom of eutrophication, and requires monitoring and management. Numerous modelling studies have been carried out to predict the behaviour of algae in freshwaters. However, in Turkey, modelling studies regarding algal growth or transport have rather been limited, particularly in river systems. The main objective of the study is to provide predictions about the intensity, timing and location of the potential algal blooms in selected streams of the Ömerli Reservoir. In order to achieve this, a formerly developed deterministic-mathematical model is applied to the selected streams of the Ömerli Reservior. Monthly field data obtained from 3 different streams of the reservoir, for 1 year is used as input data for the model application. Results indicated that the model predictions are quite reasonable in terms of expressing the relationships between environmental conditions such as, irradiance, nutrient, temperature, turbulence, and algal density change. Furthermore, the simulations also indicate an acceptable prediction of seasonal chl-a concentrations. As a result of this study, it can be said that the model simulation results fit reasonably well with the findings in the literature.
Keywords: Algebra, Boolean.; Algae.